ANALYSIS OF THE DETERMINANTS OF GRADUATES EMPLOYABILITY - Kozheski, Kristijan; Bucevska, Vesna; Janeska iliev, Aleksandra (University of Belgrade – Faculty of Organizational Sciences, 2022)
Having a university degree does not guarantee employment, hence finding and then keeping a job, especially for young people is a major issue in most economies. In the segment of Higher education institutions (HEI) everywhere around the globe pressure is growing to produce employable graduates (Grotkowska et al, 2015; Mok et al., 2016). Obtaining a complete and integrated picture of the conditions and tendencies in the labor market should inevitably be accompanied by an analysis of employability of the young, highly educated workforce. Considering that, analyse of the characteristics of graduates (young students who are in their final year of studies), as well as the factors that affect their integration in the labor market, are gaining importance as a result of increased mobility and competitiveness in the labor market. They have raised great research interest and therefore have been included in this research paper. Employability is about being capable of getting and keeping fulfilling work (Hillage & Pollard, 1998). In this context higher education institutions (HEI) worldwide have been under pressure to produce employable graduates (Grotkowska et al, 2015; Mok et al., 2016). Higher education institutions (HEI) contribute to external benefits by providing young workers with an opportunity to invest in human capital rather than being unemployed, stimulate the local economy and drive productivity spillovers (Hermannsson, Rosario, & Marcello, 2021). The objective of this paper is to determine the basic factors that affect the employability of students before graduation. Research is based upon the sample consisted of the students of Faculty of Economics – Skopje, who are in their final year of studies. The questionnaire distributed includes well designed and structured questions, so that it provided solid foundation for information to be obtained related to their demographic, economic characteristics, as well as their average grade, and their opinion about their future goals. Most of the information is based on the student’s own perception, so student self-perceived employability is considered. In this light employability of graduates has taken more importance in recent years due to the grim economic situation, growth, and an increasingly competitive global labor market. The self-perception is a critical component of employability; to comprehend the term employability, an assessment of this vital component and its elements is required. Apart from examining and understanding the students’ perceptions of their prospect of success in the graduate labour market the objective of this paper is to examine the main influence of various factors related to this field of study considering the Macedonian economy.
Keywords: labor market, graduation students, possibility of employment, determinants of employability